2020
DOI: 10.1152/ajplung.00126.2020
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on the alveolar phase of COVID-19

Abstract: COVID-19 can be divided into three clinical stages, and one can speculate that these stages correlate with where the infection resides. For the asymptomatic phase, the infection mostly resides in the nose, where it elicits a minimal innate immune response. For the mildly symptomatic phase, the infection is mostly in the pseudostratified epithelium of the larger airways and is accompanied by a more vigorous innate immune response. In the conducting airways, the epithelium can recover from the infection, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
1
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 48 publications
1
102
1
12
Order By: Relevance
“…Particularly, we found that human circulating immune cells play a key role in exacerbating inflammatory responses and the injury of alveolar-capillary-barrier induced by SARS-CoV-2. These findings provide new insight into the pathogenesis of SARS-CoV-2, in which virus-induced inflammatory responses and lung injury were possibly mediated by the complex and intrinsic cross-talk among epithelium-endothelium interface and immune cells.As known, the AT II cells have been demonstrated as the primary infected target of SARS-CoV-2 by histopathological studies[35]. In this study, we found human alveolar epithelial cells were more susceptible to SARS-CoV-2 infection than endothelial cells as identified on the chip.…”
supporting
confidence: 49%
“…Particularly, we found that human circulating immune cells play a key role in exacerbating inflammatory responses and the injury of alveolar-capillary-barrier induced by SARS-CoV-2. These findings provide new insight into the pathogenesis of SARS-CoV-2, in which virus-induced inflammatory responses and lung injury were possibly mediated by the complex and intrinsic cross-talk among epithelium-endothelium interface and immune cells.As known, the AT II cells have been demonstrated as the primary infected target of SARS-CoV-2 by histopathological studies[35]. In this study, we found human alveolar epithelial cells were more susceptible to SARS-CoV-2 infection than endothelial cells as identified on the chip.…”
supporting
confidence: 49%
“…This is a multifactorial condition, also caused by pulmonary surfactant deficit and prolonged inflammatory responses. Importantly, COVID-19 can lead to ARDS as SARS-CoV-2 can infect and impair the function of type II cells in the lungs, affecting the production of pulmonary surfactants, at the third stage of the infection [ 140 ]. Current therapeutic approaches include anti-inflammatory agents, vasodilators and surfactant replacement therapy, among others [ 141 , 142 ].…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%
“…It is postulated that the inhaled virus initially binds to nasal epithelial cells and starts propagating towards the lower respiratory tract reaching the alveoli where it infects preferentially alveolar type II cells [8]. Extensive viral replication leads to their apoptosis and cell-death, triggering through several inflammatory cascades DAD, clinically presenting as ARDS [9]. SARS-CoV-2 for its potential to induce pneumonia represents the novel infectious agent that could trigger in patients with IPF life-threatening AEs [10].…”
Section: To the Editormentioning
confidence: 99%